We all live here - Moyes, Jojo, 1969- (Pamela Dorman Books/Viking, 2025)
"Lila Kennedy has a lot on her plate. A broken marriage, two wayward daughters, a house that is falling apart, and an elderly stepfather who seems to have quietly moved in. Her career is in freefall and her love life is . . . complicated. So when her real dad-a man she has barely seen since he ran off to Hollywood thirty-five years ago-suddenly appears on her doorstep, it feels like the final straw. But it turns out even the family you thought you could never forgive might have something to teach you: about love, and what it actually means to be family"--